Improving Market Access for Leather SMEs through Marketplace and Franchise Training - Wahyu Nurjaya WK; Hamidah; Muhtarudin; Maisa Azizah Asmara (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the leather and snack processing sector in Garut Regency play an important role in the Indonesian economy, especially in creating jobs and supporting regional economic growth. However, these MSMEs face challenges such as limited market access and minimal knowledge of digital marketing and franchise business models, which impact their competitiveness. This community service program aims to empower leather and snack MSMEs by training them to utilize marketplace platforms and introducing franchise models to expand their market access. The main target is to help MSMEs under the auspices of CV. Eka Jaya Mandiri Putra in Garut by increasing their marketing capacity and expanding their reach through digital technology. The program includes needs assessment, digital marketing and marketplace training on platforms such as Tokopedia and Shopee, and guidance on franchise models as a sustainable growth strategy. Participants are trained to create accounts, optimize online stores, and analyze market trends to increase visibility and sales. In addition, they receive instructions on the concept, benefits, and risks of franchising. By improving digital skills and franchise knowledge, MSMEs are expected to be able to manage online accounts independently, expand market access, and reduce capital constraints. This initiative supports local economic growth by creating a more inclusive and competitive business ecosystem. Ultimately, this training aims to address market access limitations, helping MSMEs in Garut increase income, improve competitiveness, and thrive in an increasingly digital economy, with sustainable benefits for the local economy.